Pengaruh Pengambilan Keputusan Investasi Dan Kelayakan Investasi Saham Pada Perbankan Syariah Di Bursa Efek Indonesia - Oktadistira, Muhammad Feri; Batubara, Maryam; Nasution, Muhammad Lathief Ilhamy (CV ODIS, 2023)
The type of data used is Secondary Data which is obtained from monthly BRIS Stock Price Movement Data on the Indonesia Stock Exchange. There were 43 samples in this study. The results showed that partially the investment decision had a significant positive effect on CAPM with tcount > ttable (2.774>1.684) and a significant value of (0.017<0.05). Partially, investment feasibility has a significant negative effect on CAPM with a tcount > ttable (2.495<1.684) and a significant value of (0.008<0.05). Simultaneously Investment Decisions and Investment Feasibility have a significant effect on CAPM. With a significant value of (specify) the value of Fcount > Ftable, namely (3.868> 3.23). While the value of the coefficient of determination is 78%.